2013
DOI: 10.1038/ni.2637
|View full text |Cite
|
Sign up to set email alerts
|

Signaling via the IL-20 receptor inhibits cutaneous production of IL-1β and IL-17A to promote infection with methicillin-resistant Staphylococcus aureus

Abstract: Staphylococcus aureus causes the majority of human skin and soft tissue infections, and is a major infectious cause of mortality. Host defense mechanisms against S. aureus are incompletely understood. Interleukin (IL)-19, -20 and -24 signal through type I and type II IL-20 receptors and are associated with inflammatory skin diseases such as psoriasis and atopic dermatitis. We show here that these cytokines promote cutaneous S. aureus infection in mice by downregulating IL-1β- and IL-17A-dependent pathways. Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(132 citation statements)
references
References 52 publications
6
125
1
Order By: Relevance
“…These results corroborate the previous study by Zhao and co-workers [33], demonstrating that IFN-␥ regulates the levels of proinflammatory cytokines during S. aureus infection. Although IL-1␤ and IFN-␥ are proinflammatory cytokines, their suppression by S. aureus has been described as a mechanism for evading the host defense response [33][34][35]. Although the molecular mechanism underlying the suppression of IL-6 and TNF-␣ induced by lectin treatment in PECs infected with S. aureus remains to be elucidated, it is possible that decreases in these cytokines help to attenuate the deleterious effects of persistent inflammatory responses at the site of infection.…”
Section: Discussionmentioning
confidence: 99%
“…These results corroborate the previous study by Zhao and co-workers [33], demonstrating that IFN-␥ regulates the levels of proinflammatory cytokines during S. aureus infection. Although IL-1␤ and IFN-␥ are proinflammatory cytokines, their suppression by S. aureus has been described as a mechanism for evading the host defense response [33][34][35]. Although the molecular mechanism underlying the suppression of IL-6 and TNF-␣ induced by lectin treatment in PECs infected with S. aureus remains to be elucidated, it is possible that decreases in these cytokines help to attenuate the deleterious effects of persistent inflammatory responses at the site of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to primary infection with S. aureus crucially depends on the early production of IL-1β and IL-17 by skin-resident cells, and the downstream recruitment of neutrophils 99,100 . A recent report shows how IL-19, IL-20 and IL-24 are induced locally by S. aureus, and how these cytokines potently inhibit the generation of IL-1β and IL-17, eventually resulting in a greater severity of infection 98 . In IL-20RB-deficient mice, intradermal injection of S. aureus resulted in smaller lesions and a lower bacterial burden compared with wild-type mice, whereas co-injection of S. aureus with recombinant IL-19 or IL-20 led to more severe infection and reduced neutrophil recruitment 98 .…”
Section: Box 1 | Regulation Of the Intestinal Commensal Microbiota Bymentioning
confidence: 99%
“…One such example is Staphylococcus aureus, which infects the skin 98 . Resistance to primary infection with S. aureus crucially depends on the early production of IL-1β and IL-17 by skin-resident cells, and the downstream recruitment of neutrophils 99,100 .…”
Section: Box 1 | Regulation Of the Intestinal Commensal Microbiota Bymentioning
confidence: 99%
“…In addition, it was also found that proinflammatory IL-1β is able to upregulate IL-20 through stress-activated kinase 1 (MSK1) NF-κB-and MAPK-dependent mechanisms (Otkjaer et al, 2007). Interestingly, other investigators demonstrated that IL-20 downregulated IL-1β and IL-17A, thereby promoting infection in mice (Myles et al, 2013). Finally, IL-20 was associated with Jak/STAT3 expression and signaling in nonlesional psoriatic skin (Andrés et al, 2013).…”
Section: Interleukin-20mentioning
confidence: 93%